2009
DOI: 10.1007/s00296-009-1070-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of EMG-biofeedback in knee osteoarthritis

Abstract: This study was designed to investigate the additive effect of EMG-biofeedback in rehabilitation of knee osteoarthritis. Forty patients, aged 45-70, with the diagnosis of knee osteoarthritis according to American College of Rheumatology (ACR) criteria were taken into the study. The patients were randomly assigned in two groups. One group (n = 20) received strengthening exercise program with EMG-biofeedback while the other group (n = 20) had the same exercise program without biofeedback for 3 weeks. The clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 28 publications
3
64
0
1
Order By: Relevance
“…For patients' perception in relation to general characteristics, there was a significantly higher mean score for males than for females. These findings are similar to those of previous studies on other surgery patients [10,11]. This suggests that this study shows the most efficient way of utilizing clinical research of total knee replacement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For patients' perception in relation to general characteristics, there was a significantly higher mean score for males than for females. These findings are similar to those of previous studies on other surgery patients [10,11]. This suggests that this study shows the most efficient way of utilizing clinical research of total knee replacement.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the functional scores of the questionnaire items show that the most significant factors are age, exercise and education. The finding are consistent with the results of earlier research and suggest a need for systematic patient management [11,12]. Therefore, a program should be implemented for the groups who are characterized as having lower levels of satisfaction in terms of surgery and patients' perception.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a study on test-retest reliability of 60 PFPS patients, Bennell et al, [18] reported that VAS was high at r=.70 and another previous study employed VAS in order to evaluate pain of PFPS patients [19]. Witvrow et al [20] applied closed and open kinetic chain exercises to PFPS patients for five weeks and reported reduction in their pain, and Yilmaz et al, [11] observed that application of muscle strengthening exercise using EMG biofeedback to gonarthritis patients for three weeks resulted in decrease in their VAS values. In the present study as well, the degree of pain of the subjects with PFPS was measured prior to and after the intervention using VAS, and there were significant decreases in pain in the two other groups relative to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is usefully employed in motor learning exercise and rehabilitation process [10]. Yilmaz et al, [11] applied muscle strengthening exercise in combination with electromyography (EMG) biofeedback to knee osteoarthritis patients for three weeks and reported decrease in their pain and increased in their muscle strength. However, although closed kinetic chain exercise has been much used for rehabilitation and training of PFPS patients until recently, research which examined improvement of muscle control and response ability by self-controlling muscle activity using EMG biofeedback during closed kinetic chain exercise aimed at heightening treatment efficiency is very insufficient.…”
Section: Introductionmentioning
confidence: 99%